2018
DOI: 10.1021/acsenergylett.8b00275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cathode Material Particle Size on the Capacity of Bulk-Type All-Solid-State Batteries

Abstract: The implementation of all-solid-state batteries (ASSBs) is regarded as an important step toward next-generation energy storage systems, in particular for electric vehicles and portable electronics. This may be achieved through application of layered Ni-rich oxide cathode materials such as Li 1+x (Ni 1−y−z Co y Mn z ) 1−x O 2 (NCM) with high specific capacity and thiophosphate-based solid electrolytes. Here, the profound effect that the secondary particle size of the cathode active material has on the capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
269
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 248 publications
(279 citation statements)
references
References 26 publications
8
269
1
1
Order By: Relevance
“…[28,33,34] For this reason, sulfidebased SSBs will require coated cathode materials in order to avoid reactions between the SE and the CAM, thereby preventing the oxidation of the SE. Additionally, state-of-the-art CAMs undergo significant volume changes during lithium (de) intercalation (Figure 2c), [35,36] which often leads to detrimental contact loss within the composite cathode ( Figure 2d). [27] It will therefore be of interest to explore whether coatings can mechanically confine CAMs in order to reduce such volume changes, which may mitigate crack formation as well, or perhaps enhance adhesion within the cathode composite in order to prevent contact losses.…”
Section: Cam Coatings For Ssbs: General Considerationsmentioning
confidence: 99%
“…[28,33,34] For this reason, sulfidebased SSBs will require coated cathode materials in order to avoid reactions between the SE and the CAM, thereby preventing the oxidation of the SE. Additionally, state-of-the-art CAMs undergo significant volume changes during lithium (de) intercalation (Figure 2c), [35,36] which often leads to detrimental contact loss within the composite cathode ( Figure 2d). [27] It will therefore be of interest to explore whether coatings can mechanically confine CAMs in order to reduce such volume changes, which may mitigate crack formation as well, or perhaps enhance adhesion within the cathode composite in order to prevent contact losses.…”
Section: Cam Coatings For Ssbs: General Considerationsmentioning
confidence: 99%
“…[129] Operando XRD is well suited to analyze crystallographic changes under dynamic conditions, for example during electrochemical cycling, and several studies have reported on the lattice parameter changes of NCM CAMs with cycling, [17,18,53,61,63,104,[129][130][131][132][133][134] but only few of them revealed sufficient time and angular resolutions. Crystallographic volume changes and multiphase transformations are assumed to be responsible for the capacity fading and to be one of the main factors governing the material fatigue.…”
Section: Crystallographic Changes In Ncmmentioning
confidence: 99%
“…The size and morphological controls of the cathode particles enhanced the physical contact with the SEs, thereby contributing to the formation of a facile lithium ion pathway that consequently improved the energy density of ASSLBs. Strauss et al recently evaluated the electrochemical performance of LiNi 0.6 Co 0.2 Mn 0.2 O 2 cathode with different particle sizes ( Figure a,b) . They revealed that the initial reversible capacity strongly depended on the particle size of the cathode material.…”
Section: Recent Progress In Electrode Materialsmentioning
confidence: 99%
“…g) Solid state NMR exchange spectroscopy measurements (1D and 2D) data of the mixture III, there are large change in off‐diagonal cross‐leak intensity after the little time, high mobility of the lithium ion. a–e) Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Recent Progress In Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation